(untitled) (Trabalho & Educação, 2016)
This study sought to identify the effectiveness of Educational interventions in reducing exposure to pesticides. An integrative review was made and the selected data categorized and analyzed descriptively in two major thematic groups: Knowledge, Attitudes and Practices (KAP) and Active Community Participation. There is a strong evidence of the effectiveness of Educational interventions in reducing exposure to pesticides in different populations. A long-term analysis and work carried out in one location are needed. The active participation of the community sets as an important way for a critical review of pesticide use. KAP questionnaires are useful to highlight weaknesses in the use of pesticides, pointing out the need for interventions and evaluate their effectiveness. ___ O presente trabalho buscou identificar a eficácia de Intervenções Educacionais na redução da exposição aos agrotóxicos. Foi feita uma revisão integrativa, tendo sido os dados selecionados categorizados e analisados de maneira descritiva em dois grandes grupos temáticos: Conhecimentos, Atitudes e Práticas (KAP) e Participação Ativa da Comunidade. Existem evidências fortes da eficácia de Intervenções Educacionais na redução da exposição aos agrotóxicos em diferentes populações. Uma análise em longo prazo e de trabalhos realizados em um mesmo local se fazem necessários. A participação ativa da comunidade configura como importante caminho para uma revisão crítica do uso de agrotóxicos. Questionários KAP são úteis para destacar fragilidades em relação ao uso de agrotóxicos, apontar a necessidade de intervenções e avaliar suas efetividades.